Aldeia! Aldeia!: A formação histórica do Grupo Indígena Pitaguary e o Ritual do Toré - Magalhães, Eloi dos Santos (2007)
This work of ethnographic orientation has the objective of presenting the historical formation of the indigenous group Pitaguary and the process of reconstruction of the tradition of the ritual of the toré. I tried to show the process of political articulation in the construction of the Pitaguary ethnicity and the resulting cultural mobilization of signs and emblems of ethnic differentiation evidenced in the ritual of the toré. The intention is to reflect on the historical experience of the Pitaguary that culminated in the organization of his toré. Thus, at the same time that it produced the toré as "its tradition", the Pitaguary "gave" more force in the affirmation of the ethnic traditions of the indigenous peoples of Ceará, amplifying the distribution of some particular modality of the ritual in the Northeast.